2010
DOI: 10.1074/jbc.m110.143826
|View full text |Cite
|
Sign up to set email alerts
|

Ctr1 Is an Apical Copper Transporter in Mammalian Intestinal Epithelial Cells in Vivo That Is Controlled at the Level of Protein Stability

Abstract: Copper is an essential trace element that functions in a diverse array of biochemical processes that include mitochondrial respiration, neurotransmitter biogenesis, connective tissue maturation, and reactive oxygen chemistry. The Ctr1 protein is a high-affinity Cu ؉ importer that is structurally and functionally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 38 publications
5
106
2
Order By: Relevance
“…5A,B), suggesting that these Cu þ transporters undergo post-translational modification. In mammals, the Ctr1 Cu þ transporter is glycosylated at two positions within the N terminus [20][21][22][23] . We used a protein deglycosylation enzyme mix that removes both N-and O-glycosylation to determine whether C. neoformans Cu transporters are glycosylated.…”
Section: Resultsmentioning
confidence: 99%
“…5A,B), suggesting that these Cu þ transporters undergo post-translational modification. In mammals, the Ctr1 Cu þ transporter is glycosylated at two positions within the N terminus [20][21][22][23] . We used a protein deglycosylation enzyme mix that removes both N-and O-glycosylation to determine whether C. neoformans Cu transporters are glycosylated.…”
Section: Resultsmentioning
confidence: 99%
“…Copper transport by DMT1 therefore could be further tested in additional mammalian expression systems or in rodent models in which DMT1 is lacking or overexpressed. Meanwhile, there is strong evidence that absorption and cellular uptake of copper is served by alternative transport systems, among which are the copper transporter 1 (70,71) and an anion transporter that appears capable of transporting copper-chloride complexes (72).…”
Section: Discussionmentioning
confidence: 99%
“…The absorption of 64 Cu from an intragastric dose did not differ between DMT1 int/int and DMT1 ϩ/ϩ mice, confirming that copper does not rely on DMT1 for its absorption. We previously found that Ctr1, a high-affinity copper transporter (32), is localized to both the apical membrane and endosomal compartments of mammalian enterocytes (44). Intestinal ablation of Ctr1 in the mouse produced a severe copper deficiency and early lethality (43), establishing Ctr1 as the primary mechanism serving copper uptake at the intestinal brush border, and these studies together indicate no role for DMT1 in this process.…”
Section: G644 Role Of Intestinal Dmt1 In Metal Homeostasismentioning
confidence: 99%